PENGARUH GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA UNTUK PERIODE 2022-2024 - Novita Devi Paulus; Surenggono Surenggono (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The increasing demand for sustainable business practices has encouraged companies, particularly those in the energy sector, to implement Green Accounting and improve environmental performance as strategic efforts to enhance firm value. The energy sector is characterized by high environmental risks; therefore, transparency in environmental cost management and compliance with environmental regulations have become essential factors in strengthening investor confidence. This study aims to examine the effect of Green Accounting and environmental performance on firm value in energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research employed a quantitative approach using secondary data obtained from annual reports, sustainability reports, and PROPER data. The sample was selected using a purposive sampling technique, resulting in 54 observations. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that Green Accounting has a positive and significant effect on firm value, with a significance value of 0.046. Environmental performance also has a positive and significant effect on firm value, with a significance value of 0.038. Simultaneously, Green Accounting and environmental performance have a significant effect on firm value, with a significance value of 0.042. This study concludes that the implementation of Green Accounting and the improvement of environmental performance can enhance firm value by strengthening investor confidence and improving corporate reputation.